2020
DOI: 10.1111/and.13547
|View full text |Cite
|
Sign up to set email alerts
|

Open testicular mapping: A less invasive multiple biopsy approach for testicular sperm extraction

Abstract: This study proposes a testicular sperm extraction technique that was inspired by testicular fine‐needle aspiration. Here, we have described the technique of open testicular mapping (OTEM) and evaluated the successful sperm recovery in 92 patients with nonobstructive azoospermia (NOA). All patients underwent an OTEM biopsy. Patients were divided into two groups; group I included men with spermatozoa recovered and group 0 included men without spermatozoa recovered. Age, follicle‐stimulating hormone (FSH) level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…If no spermatozoa are found in the first testis, the contralateral testicle is approached the same way. This study demonstrated that using an approach with multiple small biopsies, it was possible to retrieve sperm in 54% of patients in the study with NOA, in addition to demonstrating that FSH levels and testicular volume were not prognostic factors for testicular sperm retrieval (15). Lopes et al developed a retrospective study, using OTEM, in which 118 patients with NOA were assessed.…”
Section: Open Testicular Mapping (Otem)mentioning
confidence: 84%
See 2 more Smart Citations
“…If no spermatozoa are found in the first testis, the contralateral testicle is approached the same way. This study demonstrated that using an approach with multiple small biopsies, it was possible to retrieve sperm in 54% of patients in the study with NOA, in addition to demonstrating that FSH levels and testicular volume were not prognostic factors for testicular sperm retrieval (15). Lopes et al developed a retrospective study, using OTEM, in which 118 patients with NOA were assessed.…”
Section: Open Testicular Mapping (Otem)mentioning
confidence: 84%
“…The SR technique described by Vieira et al ( 15 ), called Open Testicular Mapping (OTEM), was inspired by Turek's technique ( 26 ) in combination with c-TESE. This minimally invasive, low-cost, and easily reproducible approach has the advantage of not requiring the use of a surgical microscope, requiring less operative time.…”
Section: Techniques For the Treatment Of Non-obstructive Azoospermiamentioning
confidence: 99%
See 1 more Smart Citation
“…OTEM, introduced by Vieira et al., 10 has had a significant impact on our practices. This technique involves making a hole in the albuginea of the exposed testis using a 19‐G needle without a microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other methods, such as Fine Needle Aspiration Mapping (FNAP) and Open Testicular Mapping (OTEM), each have their own advantages and disadvantages. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%